Overexpression of OsFTL10 induces early flowering and improves drought tolerance in Oryza sativa L. - Fang, Maichun; Zhou, Zejiao; Zhou, Xusheng; Yang, Huiyong; Li, Meiru; Li, Hongqing (PeerJ, 2019)
Flowering time control is critically important for the reproductive accomplishment of higher plants as floral transition can be affected by both environmental and endogenous signals. Flowering Locus T-like (FTL) genes are major genetic determinants of flowering in plants. In rice, 13 OsFTL genes have been annotated in the genome and amongst them, Hd3a (OsFTL2) and RFT1 (OsFTL3) have been studied extensively and their functions are confirmed as central florigens that control rice flowering under short day and long day environment, respectively. In this report, a rice OsFTL gene, OsFTL10, was characterized, and its function on flowering and abiotic stress was investigated. The expression level of OsFTL10 was high in young seedlings and shown to be induced by GA3 and drought stress. Overexpression of OsFTL10 resulted in earlier flowering in rice plants by up to 2 weeks, through up-regulation of the downstream gene OsMADS15. OsFTL10 also regulated Ehd1 and OsMADS51 through a feedback mechanism. The OsFTL10 protein was also detected in both nucleus and cytoplasm. Furthermore, yeast two hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) results show that OsFTL10 could interact with multiple 14-3-3s, suggesting that OsFTL10 might function in a similar way to Hd3a in promoting rice flowering by forming a FAC complex with 14-3-3, and OsFD1. Further experiments revealed that constitutive expression of OsFTL10 improved the drought tolerance of transgenic plants by stimulating the expression of drought responsive genes. These results suggest that rice FTL genes might function in flowering promotion and responses to environmental signals.
Keywords: Oryza sativa L.; OsFTL10; Flowering; Drought tolerance; Transgenic plants